The role of superior hemorrhoidal vein ectasia in the preoperative staging of rectal cancer - Lucarelli, Nicola Maria; Mirabile, Alessandra; Maggialetti, Nicola; Morelli, Chiara; Calbi, Roberto; Bartoli, Simona; Avella, Pasquale; Saccente, Domenico; Greco, Sara; Ianora Stabile, Antonio Amato (Frontiers in Oncology, 2024)
The prognosis of colorectal cancer has continuously improved in recent years thanks to continuous progress in both the therapeutic and diagnostic fields. The specific objective of this study is to contribute to the diagnostic field through the evaluation of the correlation between superior hemorrhoidal vein (SHV) ectasia detected on CT and TNM examination and MRF invasion in the preoperative staging of rectal cancer.Between January 2018 and April 2022, 46 patients with histopathological diagnosis of rectal cancer were retrospectively enrolled and the diameter of the SHV was evaluated by CT examination.The cut-off value for SHV diameter used is 3.7 mm. The diameter was measured at the level of S2 during portal venous phase after 4x image zoom to reduce the interobserver variability. The parameters evaluated were tumour location, detection of MRF infiltration (defined as the distance < 1 mm between the tumour margins and the fascia), SHV diameter, detection of mesorectal perilesional lymph nodes, detection of metastasis.67.39% (31/46) of patients had SHV ectasia. All patients with MRF infiltration (4/46, 7.14%) presented SHV ectasia (average diameter 4.4 mm) and SHV was significantly related with the development of liver metastases at the moment of primary staging and during follow-up.SHV ectasia may be related to metastasis and MRF involvement therefore it could become a tool for preoperative staging of rectal cancer.